The Correlation of the Eucharist with Christ: Vermigli's Oxford Treatise and Disputation on the Eucharist (1549) - Boutin, Maurice (Toronto journal of theology, 2010)
Why does correlation work perfectly between the Eucharist and Christ, whereas neither the notion of transubstantiation nor Chalcedonian Christology appears in Scripture? Although Vermigli keeps repeating that Scripture provides no basis for transubstantiation based on the distinction between substance and accidents, he relies on the Chalcedonian Formula. At least in the Treatise and in the Disputation Vermigli does not question to what extent these distinctions are "according to the Scriptures." Is it because Chalcedonian Christology is older than transubstantiation defined by the fourth Lateran Council in 1215? This should not be viewed as the proper explanation for Vermigli's position against transubstantiation. Rather, the human nature of Christ is not just an accident. Human nature does not need to be understood that way in order to secure the real presence of God in Jesus Christ. Likewise, the "nature and substance" of bread does not need to "go away" or be "cast away" in order to make room for the substance of Christ and thus ensure the real presence of Christ in the Eucharist. Otherwise, transubstantiation could be viewed as only a continuation—or a revival—of docetism: to contend that through transubstantiation "it seems to be bread, but is not" amounts to saying that Christ's flesh and body was not true flesh, but only an appearance. The analysis of this controversy regarding the presence of Christ in the Eucharist can be best understood as a chapter of what can be called "indirect Christology."